Ellipsis and its translation from Arabic into Malay language: An analytical study - Abd Rahman L.; Yeob S.J.; Abdul Rahman A.K. (Kolej University Islam Sultan Azlan Shah, 2024)
Ellipsis is one of the linguistic phenomena which can be found in Quranic and Arabic texts. Ellipsis is also used to denote specific meanings and purposes in a text. It is one of the conjunctional elements in the text linguistics that functionsas cohesion which connects parts of the text and provides explicit and implicit meanings accordingly that could be comprehended and guessed by the readers from the text. Readers could benefit from the ellipsis in a text by referring to the previous sentences in other paragraphs in order to understand the text. This paper, thus, attempts to study this linguistic phenomenon by analyzing the translation of the Quranic text in order to investigate the techniquesof translating a foreign text as well as to crystalize possible ways in dealing with ellipsis by the translators.This is to ascertain the importance of cohesion in a text as well as to facilitate and assist the translators to use sensible and correct translation techniques in dealing with ellipsis in the Quran.Ways of dealing with ellipsis are vary between translators that some of them are very concern about it and highlight it in their translation, but some only mention it briefly; and even worse, some of them just neglect it totally. Intrinsically, the translations of ellipsis in the Quranic text are very helpful and essential in providing clear and accurate meaning of the text as well as to maintain cohesiveness between the translated verses.